Poverty and Peace in the Portuguese Speaking African Countries - Cristina Rodrigues Udelsmann, Ana Bénard da Costa (dir.) (Centro de Estudos Internacionais, 2009)
As the end result of a multidisciplinary investigation project conducted in Africa (PTDC/AFR/64207/2006, Fundação para a Ciência e a Tecnologia), this publication about Poverty and Peace in the Portuguese-speaking African Countries has the purpose, on one hand, of presenting the main conclusions of the studies conducted in these countries and, on the other, to provide a collection of guidelines for future research relevant to the comprehension of the combination of both phenomena.